MEDIAL SURAL ARTERY PERFORATOR FLAP: A VERSATILE OPTION FOR SOFT TISSUE RECONSTRUCTION OF HEAD AND NECK AND LIMBS - Khalid, Farrukh Aslam; Rehman, Saif ur; Haq, Ata Ul; Riaz, Ahsan; Saleem, Muhammad; Rabbani, Muhammad Jibran; Amin, Muhammad; Mujahid, Abdul Malik; Alvi, Hamid Fazeel; Tarar, Moazzam Nazeer (Journal of Ayub Medical College Abbottabad, 2018)
Background: To assess the outcome of Medial Sural Artery Perforator Flap (MSAP Flap) as an option for the soft tissue reconstruction of head and neck and limbs. Methods: This descriptive case series was conducted at Jinnah Burn and Reconstructive Surgery Center, Lahore during October 2016 to August 2017. All patients in whom MSAP flap (free and pedicled) was performed for reconstruction are included. Patients were followed at one week and one month after the discharge and data was entered into the proformas. Results: In total, 18 patients were operated with this flap. Free and pedicled MSAP flap were performed for reconstruction of soft tissue defects in the head and neck and the lower limb. The maximum dimensions of the flap were 14 cm length and 10 cm width. The maximum pedicle length was 16cm. All flaps survived and showed good outcome. There was necrosis of the distal margin of a pedicled flap, but no case of venous congestion and flap failure was observed. The flap donor site was closed primarily in 7 patients while split skin graft was used in the rest of the patients. Conclusion: The MSAP flap provides a thin skin paddle and has minimal donor site morbidity as compared to the other options. It is a good addition to the armamentarium of perforator flaps which are thin and pliable, can be harvested by two team approaches, under the tourniquet and has a hidden donor site. Keywords: Medial Sural artery; Perforator flap; Soft tissue coverage; Reconstruction